Mudik during the Covid-19 pandemic, anxiety, and depression among students in Indonesia - Metta Rahmadiana; Supra Wimbarti; Ira Paramastri; Atik Triratnawati (Berita Kedokteran Masyarakat (BKM), 2021)
Purpose: This study explores the occurrence and different levels of anxiety and depression among male and female students who perform or do not perform mudik (homecoming). Investigate the primary source of COVID-19 related information among students. Methods: Online questionnaires consisting of the self-report level of anxiety and depression were delivered to study participants after completing the online informed consent. Quantitative analysis was conducted using the IBM SPSS version 20.0.Results: From a total of 2018 study participants, n=936 were students. Depression (M=8.68; SD= 5.45) was higher among students who did not perform mudik. Meanwhile, the prevalence rate of depression (M=7.18; SD=4.99) was also higher among students who performed mudik. A significant difference [sig (2-tailed) = 0.017; p <0.05)] regarding the level of anxiety was reported higher among female students (M=7.80; SD=4.6) than male students (M=7.03; SD=4.7) and no significant difference [sig (2-tailed) = 0.173; p> 0.05] was reported for the level of depression between male and female students. Instagram was reported as the primary source of COVID-19 related information. Conclusion: This current study supports the notion regarding the occurrence of common mental disorders among students as an impact of the COVID-19 pandemic, regardless of whether homecoming was performed or not. Different levels of anxiety and depression were reported between the male and female student population.